A study on quality of information gathered by principal in IT service outsourcing. (18th July 2008) - Lin, Deng; Xia, Yuanqiang; Cheng, Hongxing
The quality of the information directly affects the optimal contract and the expected output in principal-agent theory. In this paper, with Bayesian rules, we design an IT service outsourcing model under the framework of the principal-agent in order to analyse the effects of the quality of information gathered by principal on optimal contract and expected payoff to him and discuss the strategic problem how principal uses these high-quality information. It is significant to explain the information gathering in the outsourcing of IT services and guide enterprise's services outsourcing with these conclusions.